Crime and birth rate in Ukraine: modelling and statistical analysis - O. F. Shevchuk (Law and Safety)
The article is devoted to empirical testing of the hypothesis that there is a correlation between the birth rate and the overall level of crime in Ukraine. A detailed analysis of the relevant correlation field confirms the hypothesis, but such a relationship, as shown by the calculation of determination coefficients, depends on the level of lag between the indicators and reaches its maximum value at a time lag of two years between them. The study has also identified an atypical area of direct linear relationship between birth rate and crime (2018–2021), which does not correspond to the general reverse trend.